KARAKTERISTIK FISIK DAN KIMIA TEPUNG BUAH NAGA MERAH (Hylocereus polyrhizus) SEBAGAI BAHAN BAKU MINUMAN INSTAN - , DEA PUTRI DARANINGGAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Degenerative disease becomes the biggest causal of death in the world. The change of epidemic dominance disease from infectious diseases to non-infectious diseases is the effect of increasing degenerative disease prevalence. Risk factor which is mostly as the causal is unhealthy food consumption. Dragon fruit (Hylocereus sp